مستوى الشفقة بالذات لدى الراسبين في إمتحان شهادة البكالوريا للموسم2022-2023 - معاش سالمة; نوار شهرزاد (University of Eloued جامعة الوادي, 2024)
هدفت الدراسة الحالية إلى التعرف على مستوى الشفقة بالذات لدى عينة من التلاميذ الراسبين في إمتحان شهادة البكالوريا بثانوية مالك بن نبي بالرويسات.حيث أجريت على عينة قوامها 30 تلميذ وتلميذة ولتحقيق أهداف الدراسة إعتمدنا مقياس الشفقة بالذات لكسرتين نيف (2003) تعريب السيد عبد الرحمان و أخرون منتهجين في ذلك المنهج الوصفي الاستكشافي لإعتباره المناسب في مثل هذه الدراسات. حيث توصلت نتائج الدراسة إلى وجود مستوى مرتفع من الشفقة بالذات لدى أفراد العينة، مع عدم وجود فروق ذات دلالة إحصائية في درجات أفراد العينة تعزى للمتغيرات التالية الجنس ، الإعادة السابقة وكذا لمتغير تخصص الدراسي . Abstract: The current study aims to identify the level of self-compassion in a sample of the flunkers in the baccalaureate exam at Malik Ben Nabi- Rouissat- High School. A sample of 30 pupils (male and female ). In order to achieve the study's objectives , we have adopted self-compassion scale by Kristin Neff (2003) translated to Arabic by Abd El Rahman Et al .We used the descriptive exploratory method because it is suitable in such cases . The results of the study revealed a high level of self-compassion among the sample members, with no statistically significant differences in the sample members' scores attributable to the following variables: sex, previous reinstatement, as well as the flunker specialty variable
Keywords: شفقة بالذات; تلاميذ البكالوريا راسبين; بكالوريا: self-compassion; flunkers in the baccalaureate exam; baccalaureate exam